The benefits of newborn screening for cystic fibrosis: The Canadian experience - Mak, D.Y.F.; Sykes, J.; Stephenson, A.L.; Lands, L.C. (Journal of cystic fibrosis, 2016)
The impact of newborn screening (NBS) for cystic fibrosis (CF) on early indicators of long-term health was evaluated in the context of government-sponsored healthcare and access to current therapies. Using data from the Canadian CF Registry between 2008 and 2013, we compared the rates of respiratory infections and markers of nutritional status in those diagnosed through NBS to those who were diagnosed clinically within the same time period using Mann–Whitney and Fischer's exact test as appropriate. The study included 303 subjects, 201 in the NBS group and 102 in the non-NBS group. NBS patients were diagnosed earlier and had their first clinic visit at a younger age. Pancreatic insufficiency was less common in NBS patients. The incidence of Pseudomonas aeruginosa and Staphylococcus aureus were lower in NBS patients. After adjusting for age at clinic visit, gender, pancreatic status, and Pseudomonas aeruginosa infection status, mean z-scores for weight-for-age and height-for-age were higher in NBS patients, with no differences in BMI-for-age. NBS programs for CF lead to improved long-term health outcomes for the CF population.